Transformasi Seni Karawitan di Era Digital dan Pelestarian dalam Perkembangan Teknologi - Hadi Sasono, Ipa; Setiawan, Sigit (Universitas Nahdlatul Ulama Blitar, 2025)
This research aims to examine the transformation of Karawitan art in the digital era and explore the challenges and opportunities that arise in preserving it in the context of technological developments. Karawitan art, as an integral part of Indonesian culture, faces great challenges in maintaining its authenticity and existence amidst the rapid development of digital technology. Using a qualitative approach, this study collected data through in-depth interviews, field observations, and digital content analysis, and identified key themes relating to digital transformation, challenges in preservation, and opportunities offered by technology. The results show that digital technology provides great opportunities in introducing the art of Karawitan to a global audience through digital platforms such as YouTube, Spotify, and social media. However, the main challenges faced are the loss of deep traditional experiences and the difficulty in maintaining a balance between tradition and technological innovation. Nonetheless, technology also opens up opportunities for the preservation of the art of Karawitan through learning apps, digital recording and international collaboration. This research concludes that while technology can play an important role in the preservation and development of Karawitan, it is important to maintain traditional cultural values to keep the art relevant and authentic in the digital age.